Cardiac MRI Based Left Ventricular Global Function Index: Association with Disease Severity in Patients with ICD for Secondary Prevention - Andreas Leonhard Schober (MDPI AG, 2021)
Left ventricular (LV) ejection fraction (LVEF) is the most widely used prognostic marker in cardiovascular diseases. LV global function index (LVGFI) is a novel marker which incorporates the total LV structure in the assessment of LV cardiac performance. We evaluated the prognostic significance of LVGFI, measured by cardiovascular magnetic resonance (CMR), in predicting mortality and ICD therapies in a real-world (ICD) population with secondary ICD prevention indication, to detect a high-risk group among these patients. In total, 105 patients with cardiac MRI prior to the ICD implantation were included (mean age 56 ± 16 years old; 76% male). Using the MRI data for each patient LVGFI was determined and a cut-off for the LVGFI value was calculated. Patients were followed up every four to six months in our or clinics in proximity. Data on the occurrence of heart failure symptoms and or mortality, as well as device therapies and other vital parameters, were collected. Follow up duration was 37 months in median. The mean LVGFI was 24.5%, the cut off value for LVGFI 13.5%. According to the LVGFI Index patient were divided into 2 groups, 86 patients in the group with the higher LVGFI und 19 patients in the lower group. The LVGFI correlates significantly with the LVEF (r = 0.642, p < 0.001). In Kaplan–Meier analysis, a lower LVGFI (<13.5%) was associated with a higher rate of mortality and rehospitalization (p = 0.002). In contrast, echocardiographic LVEF ≤ 33% was not associated with a higher rate of mortality or rehospitalization. Multivariate Cox-regression analysis revealed a lower LVGFI (p = 0.025, HR = 0.941; 95%-CI 0.89–0.99) and diabetes mellitus (p = 0.027, HR = 0.33; 95%-CI 0.13–0.88) as an independent predictor for mortality and rehospitalization. There was no association between the combined endpoint and the LVEFMRT, LVEFecho, NYHA > I, the initial device or a medication (each p = n.s.). Further, in Kaplan–Meier analysis no association was evident between the LVGFI and adequate ICD therapy (p = n.s.). In secondary prevention ICD patients reduced LVGFI was shown as an independent predictor for mortality and rehospitalization, but not for ICD therapies. We were able to identify a high-risk collective among these patients, but further investigation is needed to evaluate LVGFI compared to ejection fraction, especially in patients with an elevated risk for adverse cardiac events.